PERJANJIAN KREDIT ANTARA NASABAH DENGAN PIHAK BANK PEMBANGUNAN DAERAH KALIMANTAN TIMUR DI TINJAU MENURUT PASAL 1320 Jo 1338 KITAB UNDANG-UNDANG HUKUM PERDATA - Hasibuan Monica Helend (Universitas 17 Agustus 1945 Samarinda, 2014)
Abstract As the direction of development in the field of business law needs to be improved maintaining public order based on justice and able to protect the public as one of the requirements for the creation of a stable national. These efforts will further encourage the development of people's creativity, vitality of life and broaden people's participation in the implementation of development in all fields. As it is known that Indonesia is a nation that is growing and development is currently being promoted and developed rapidly. In large cities there are many buildings skyscrapers standing strong and the government apparatus is in full swing to make improvements everywhere. Companies are increasingly spreading its wings to get optimal results by expanding its network to the entire archipelago.